Sex-Specific Accumulated Oxygen Deficit During Short- and Middle-Distance Swimming Performance in Competitive Youth Athletes - Massini, Danilo Alexandre [UNESP] (2023)
Introduction: Since sex-specific accumulated oxygen deficit (AOD) during high-intensity swimming remains unstudied, this study aimed to assess AOD during 50, 100, and 200 m front-crawl performances to compare the responses between sexes and analyse the effect of lean body mass (LBM). Methods: Twenty swimmers (16.2 ± 2.8 years, 61.6 ± 7.8 kg, and 48.8 ± 11.2 kg LBM—50% males) performed 50, 100, and 200 m to determine accumulated oxygen uptake (V̇O2Ac). The swimmers also performed an incremental test from which five submaximal steps were selected to estimate the oxygen demand (V̇O2demand) from the V̇O2 versus velocity adjustment. V̇O2 was sampled using a gas analyser coupled with a respiratory snorkel. AOD was the difference between V̇O2demand and V̇O2Ac, and LBM (i.e. lean mass not including bone mineral content) was assessed by dual-energy X-ray absorptiometry (DXA). Results: A two-way ANOVA evidenced an AOD increase with distance for both sexes: 19.7 ± 2.5 versus 24.9 ± 5.5, 29.8 ± 8.0 versus 36.5 ± 5.8, and 41.5 ± 9.4 versus 5.2 ± 11.9 ml × kg−1, respectively, for 50, 100, and 200 m (with highest values for females, P < 0.01). Inverse correlations were observed between LBM and AOD for 50, 100, and 200 m (r = − 0.60, − 0.38 and − 0.49, P < 0.05). AOD values at 10 and 30 s elapsed times in each trial decreased with distance for both sexes, with values differing when female swimmers were compared to males in the 200 m trial (at 10 s: 2.6 ± 0.6 vs. 3.4 ± 0.6; and at 30 s: 7.9 ± 1.7 vs. 10.0 ± 1.8 ml × kg−1, P < 0.05). Conclusion: LBM differences between sexes influenced AOD values during each trial, suggesting that reduced muscle mass in female swimmers plays a role on the higher AOD (i.e. anaerobic energy) demand than males while performing supramaximal trials.